Impaired Diastolic Function Predicts Improved Ischemic Myocardial Flow by Mechanical Left Ventricular Unloading in a Swine Model of Ischemic Heart Failure - Sakata, Tomoki; Watanabe, Shin; Mazurek, Renata; Mavropoulos, Spyros; Romeo, Francisco; Yamada, Kelly P.; Ishikawa, Kiyotake (Frontiers in Cardiovascular Medicine, 2022)
Background: Impact of mechanical left ventricular (LV) unloading on myocardial tissue perfusion and its regulating factors remain unclear. This study was conducted to elucidate the predictors of regional blood flow (RBF) improvement by mechanical LV unloading. Materials and Methods: One to four weeks after percutaneous induction of myocardial infarction (MI), Yorkshire pigs (n=15) underwent mechanical LV unloading using Impella CP. Hemodynamic parameters were collected prior to LV unloading. RBF in infarct, border and remote myocardium were measured by fluorescent microsphere injections before and 120 minutes after LV unloading. Results: RBF showed variable responses to mechanical LV unloading. While infarct RBF improved in general (0.33±0.13 to 0.42±0.19 mL/min/g, p=0.06), there were a few pigs that showed little improvement. Meanwhile, there were no clear trends in the border (1.07±0.47 to 1.02±0.65 mL/min/g, p=0.73) and remote myocardial RBF (1.25±0.52 to 1.23±0.68 mL/min/g, p=0.85). In the simple linear regression analysis, cardiac output, mean pulmonary arterial wedge pressure, mean left atrial pressure, minimum LV pressure, end-diastolic LV pressure, maximum dP/dt, slope of end-diastolic pressure-volume relationship (EDPVR) and end-diastolic wall stress were significantly associated with % change of infarct RBF. In the multiple regression model, slope of EDPVR and maximum dP/dt remained as independent predictors of infarct RBF change. Conclusion: Steeper EDPVR and lower maximum dP/dt were associated with increased blood perfusion in the infarct area after LV unloading. Our data suggests mechanical LV unloading is more beneficial in post-MI patients with high diastolic pressure associated with increased LV stiffness and in those with worse cardiac contractility.